Compound Flooding: Dependence at Sub-daily Scales Between Extreme Storm Surge and Fluvial Flow - Robins, Peter E.; Lewis, Matt J.; Elnahrawi, Mariam; Lyddon, Charlotte; Dickson, Neil; Coulthard, Tom J. (Frontiers in Built Environment, 2021)
Estuaries are potentially exposed to compound flooding where weather-driven extreme sea levels can occur synchronously with extreme fluvial discharge to amplify the hazard. The likelihood of compound flooding is difficult to determine due to multiple interacting physical processes operating at sub-daily scales, and poor observation records within estuaries with which to determine potential future probabilistic scenarios. We hypothesise that fluvial extremes can occur within the peak of the surge in small/steep catchments because of rapid runoff times, whilst the length-scale in larger/flatter catchments will result in fluvial and marine extremes being out-of-phase. Data (15-minute river flow and hourly sea level) spanning 40 years were analysed to assesses the behaviour and timings of fluvial and sea level extremes in two contrasting estuaries: Humber and Dyfi (UK). Compound events were common in the Dyfi, a small/steep catchment on Britain’s west coast with fast fluvial response times. Almost half of the 937 skew-surge events (95th-percentile) occurred within a few hours of an extreme fluvial peak, suggesting that flood risk is sensitive to the storm timing relative to high tide – especially since flows persisted above the 95th-percentile typically for less than 12 hours. Compound events were more frequent during autumn/winter than spring/summer. For the Humber, a larger/flatter catchment on the east coast with slower fluvial response times, extreme fluvial and skew-surge peaks were less frequent (half as many as the Dyfi) and compound events were less common (15% of events co-occurred). Although flows in the Humber persisted above the 95th-percentile for typically between one and four days, hence overlapping several high tides and possibly other surges. Analysis of 56 flooding events across both estuaries revealed: (1) flooding is more common in the Dyfi than Humber; (2) Dyfi flooding is driven by 99th-percentile flows lasting hours and co-occurring with a 95th percentile skew-surge; (3) Humber flooding was driven by 95th-percentile flows lasting days, or surge-driven – but rarely co-occurring. Our results suggest that compound flooding studies require at least hourly data (previous analyses have often used daily-means), especially for smaller systems and considering the potential intensification of rainfall patterns into the future.